Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Persamaan Linear Satu Variabel Berdasarkan Teori Kastolan - Katarina Yasinta Ndek; Vivi Suwanti; Sumadji (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This study aims to find out student errors in solving linear equations of one variable based on Kastolan's theory. This study is descriptive research. The data collection technics that are used are 1) a test to solve the story problems of linear equations of one variable based on the Kastolan theory, 2) an interview with all subjects, and 3) documentation. The subjects of this study were seventh-grade students of SMP Negeri 2 Boleng, West Manggarai Regency, NTT with 20 students categorized based on their errors in Kastolan theory. The study results showed that 1) 36.66% of students made conceptual errors in understanding the concept of the meaning of the problem, 2) 58.33% of students made procedural errors by not following the steps in solving the problem and not writing the conclusion at the end of the answer, and 3) 35% of students made operations technical errors in calculating the value of solving problems and errors in writing variables and constants. The factors that are causing these errors because students do not understand the meaning of the questions, are not serious in answering questions and do not review the results of the assignment